How does EMU affect the dollar and the yen as international reserve and investment currencies? - Michael Frenkel; Jens Søndergaard (Deutsche Bank Research, 1999)
Since EMU represents a currency area with a GDP level and a world market share comparable to the United States, it is widely expected that the euro will become an important international currency. This paper suggests simple methods how to quantify the effects that EMU may exert on the roles of the dollar and the yen as the other major international currencies. Estimates presented indicate that the euro may indeed lead to a significant decline in the market share of the dollar as an official reserve currency of central banks and as an investment currency of private portfolios. These effects hinge on the assumption that the euro will achieve a reputation similar to that of the deutschmark before EMU. The projected shifts can be expected to materialize only in the medium term so that no immediate abrupt changes in the demand for dollars will occur.
Keywords: F02; F21; F36; 330; International Economic Integration; Long-Term Capital Movements; Financial Aspects of Economic Integration; Europäische Wirtschafts- und Währungsunion; Euro; US-Dollar; Yen; Reservewährung; Portfolio-Investition; Devisenmarkt; Schätzung; Welt